A review on l-ribose isomerases for the biocatalytic production of l-ribose and l-ribulose. (July 2021) - Mahmood, Shahid; Iqbal, Muhammad Waheed; Zhang, Wenli; Mu, Wanmeng
Graphical abstract: Highlights: l -Ribose and l -ribulose are rare sugars and isomers of each other. l -Ribose and l -ribulose have great importance in the field of food and pharmaceutical. l -Ribose isomerase can catalyze various aldoses into their respective ketoses. The most preferable substartes for l -ribose isomerase were l -ribose and l -ribulose. l -Ribose isomerase can also catalyze the reversible isomerization between many other rare sugars. Abstract: Presently, because of the extraordinary roles and potential applications, rare sugars turn into a focus point for countless researchers in the field of carbohydrates. l -ribose and l -ribulose are rare sugars and isomers of each other. This aldo and ketopentose are expensive but can be utilized as an antecedent for the manufacturing of various rare sugars and l -nucleoside analogue. The bioconversion approach turns into an excellent alternative method to l -ribulose and l -ribose production, as compared to the complex and lengthy chemical methods. The basic purpose of this research was to describe the importance of rare sugars in various fields and their easy production by using enzymatic methods. l -Ribose isomerase (L-RI) is an enzyme discovered by Tsuyoshi Shimonishi and Ken Izumori in 1996 from Acinetobacter sp. strain DL-28. L-RI structure was cupin-type- β -barrel shaped with a catalytic site between two β -sheets surrounded by metal ions. The crystal structures of the L-RI showed that it contains a homotetramer structure. Current review have concentrated on the sources, characteristics, applications, conclusions and future prospects including the potentials of l -ribose isomerase for the commercial production of l -ribose and l -ribulose. The MmL-RIse and CrL-RIse have the potential to produce the l -ribulose up to 32% and 31%, respectively. The CrL-RIse is highly stable as compared to other L-RIs. The results explained that the L-RIs have great potential in the production of rare sugars especially, l -ribose and l -ribulose, while the immobilization technique can enhance its functionality and properties. The present study precises the applications of L-RIs acquired from various sources for l -ribose and l -ribulose production.